Microneedling with platelet-rich plasma versus microneedling with vitamin C in treatment of acne scars: comparative study - Khaled M. Tawfik; Mahmoud A.E Makki; Fatma E.-Z.M Mahmoud (Wolters Kluwer Medknow Publications, 2023)
Background and aim Postacne scars may affect about 95% of patients with past history of acne that is related to its duration and severity of. Treatment of acne scarring is challenging. Microneedling with platelet-rich plasma (PRP) or vitamin C is a new, simple, and effective treatment modality for such scars. The authors aimed to compare between microneedling plus PRP versus microneedling plus vitamin C in treatment of postacne scars. Patients and methods This is a comparative study that was carried out on 20 patients (their ages ranged from 22 to 37 years). They are four males and 16 females, they presented with postacne scars. The patients were divided randomly to receive microneedling plus PRP on one side of the face, and microneedling plus vitamin C on the other side. Results The authors found a significant improvement of atrophic acne scars, with significant reduction in the number of acne scars as well as Goodman score after treatment by microneedling plus PRP as well as microneedling plus vitamin C, moreover, most of the patients were satisfied after treatment with no significant difference between both treatment methods. Microneedling with PRP and vitamin C was well-tolerated with no major adverse events that were observed. Conclusion PRP as well as vitamin C combined with microneedling is a safe, effective, and promising option in treatment of acne scars.